Case Report: Identification of microduplication in the chromosomal 2p16.1p15 region in an infant suffering from pulmonary arterial hypertension - Wang, Xun; Zhang, Zeying; Zuo, Wanyun; Wang, Dan; Yang, Fan; Liu, Qiming; Xiao, Yunbin (Frontiers in Cardiovascular Medicine, 2023)
This study reports the first case of a patient with chromosome 2p16.1p15 microduplication syndrome complicated by pulmonary arterial hypertension (PAH).Atrial septal defect was found via conventional echocardiography when the female infant was admitted to the hospital suffering from dyskinesia and developmental delay, which was not taken seriously and treated at that time. Two years later, preoperative right heart catheterization for atrial septal defect closure revealed a mean pulmonary artery pressure (mPAP) of 45 mmHg. After targeted drug therapy, the mPAP was reduced and the condition tended to be stable. A genomic copy number duplication (x3) of at least 2.58Mb in the 2p16.1p15 region on the paternal chromosome was revealed. This genomic region involves multiple OMIM genes including BCL11A, EHBP1, FAM161A, PEX13, and REL. EHBP1 promotes a molecular phenotypic transformation of pulmonary vascular endothelial cells and is thought to be involved in this infant's rapidly developing PAH. Collectively, our findings add to the knowledge of the genes involved and the clinical manifestations of the 2p16.1p15 microduplication syndrome. Clinicians should be alert to the possibility of PAH and take early drug intervention when facing patients with 2p16.1p15 microduplications.